MODEL PEMBACAAN KRITIS TEKS-TEKS KEISLAMAN KAUM FEMINIS - Azzuhri, Muhandis (MUWAZAH, 2014)
Abstract : Study feminism can not be separated from theological studies. Almost all religions have bad treatments against women. The position of women in some religions are placed as "The Second Sex" and that religion perceives something usually considered "as it should be" (what exactly), instead of "as it is" (whatever they are). Riffat Hassan and Amina Wadud form of interpreting the verses of the Qur'an which is far from the spirit of liberation theology with a feminine approach. Feminism is understood as the liberation of all the oppression of humanity. Abstrak : feminisme Studi tidak dapat dipisahkan dari studi teologi. Hampir semua agama memiliki perawatan yang buruk terhadap perempuan. Posisi perempuan dalam beberapa agama ditempatkan sebagai "The Second Sex" dan agama yang merasakan sesuatu yang biasanya dianggap "sebagaimana mestinya" (apa sebenarnya), bukan "karena" (apa adanya). Riffat Hassan dan Amina Wadud bentuk menafsirkan ayat-ayat Al-Qur'an yang jauh dari semangat teologi pembebasan dengan pendekatan feminin. Feminisme dipahami sebagai pembebasan dari penindasan kemanusiaan.